The Role of Tumor Budding as a Prognostic Factor in Colorectal Adenocarcinoma - Rianti, Andi Marcha; Miskad, Upik Anderiani; Cangara, Muhammad Husni; Wahid, Syarifuddin; Achmad, Djumadi; Tawali, Suryani (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Colorectal cancer is one of the most prevalent malignancies worldwide. Tumor budding has emerged as a potential prognostic indicator in colorectal adenocarcinoma. Objective: This study aimed to analyze the relationship between tumor budding and histopathological grade, lymphovascular invasion, and lymph node metastasis in colorectal adenocarcinoma, and to assess the potential of tumor budding as a prognostic factor. Methods: A cross-sectional study was conducted using 93 colorectal adenocarcinoma samples. The association between tumor budding and histopathological grade, lymphovascular invasion, and lymph node metastasis was evaluated using the Chi-square and Mann-Whitney tests. Results: Among the 93 samples, a significant difference in tumor budding scores was found between cases with and without lymphovascular invasion (p = 0.003). However, no significant association was observed between tumor budding scores and histopathological grade (p = 0.685) or lymph node metastasis (p = 0.092). Additionally, a significant correlation was found between lymphovascular invasion and lymph node metastasis (p < 0.001). Conclusion: Tumor budding may serve as an important prognostic factor in colorectal adenocarcinoma, particularly in its association with lymphovascular invasion